Determination of black carbon and nanoparticles along glaciers in the Spitsbergen (Svalbard) region exploiting a mobile platform. (December 2017) - Spolaor, Andrea; Barbaro, Elena; Mazzola, Mauro; Viola, Angelo P.; Lisok, Justyna; Obleitner, Friedrich; Markowicz, Krzysztof M.; Cappelletti, David
Abstract: An innovative approach to characterize concentration of atmospheric aerosol particles and air mass layering along the elevation profile of glaciers is presented for the first time and validated, exploiting low weight and fast response sensors deployed on a snowmobile. Two micro-Aethalometers for black carbon measurements and a miniature Diffusion Size Classifier (miniDisc) for total aerosol concentration (airborne particles) in the 14–260 nm range were used. Test experiments were conducted in the Arctic (Svalbard) in Spring (2016). Three glaciers in the Spitsbergen region were considered for this exploratory study, the Austre Brøggerbreen, the Edithbreen and the Kongsvegen. The Austre Brøggerbreen and Edithbreen were considered as test sites to setup the experiment, to optimize the sampling strategy and to identify some basic experimental artefacts. Kongsvegen glacier was chosen for the main case study, extending from the Kongsfjorden coast to roughly 700 m above sea level for a total length of ca. 25 km and with a nearly constant elevation gradient. The obtained results were rather consistent for the three glaciers and show an increase of nanoparticles with altitude. Black carbon concentration show stationary to decreasing trends going from the bottom to the top of the glaciers. These observations indicate a very active secondary aerosol formation at the highest elevations, responsible for the increase concentration of ultrafine particles at the glacier top. On the other side, black carbon shows higher levels at the lower altitudes of the glacier. This is indicative that in absence of a long-range transport as demonstrated by calculated back trajectories, black carbon might have accumulated due to the effect of katabatic winds flow along the glacier profile. The results obtained were compared and are largely consistent with the observations from concurrent soundings with a tethered balloon experiment conducted in the nearby site of Ny-Ålesund. The proposed experimental design opens new perspectives for future experiments, which may be of relevance for the understanding of black carbon and dry dust deposition on the glacier surface, which may impact the melting of ice and snow. The investigations also contribute to better understanding of the transport and surface exchange processes acting within the atmospheric layer over glacier surface. Highlights: Innovative atmospheric experiment based on continuous measurements using snowmobile. Aerosol and BC profile along the Kongsvegen glacier, Spitsbergen, Svalbard. Study the exchange processes acting within the atmospheric layer over glacier surface. Comparison between the free atmosphere structure and the atmosphere above the glacier.